2019
DOI: 10.3390/s19245464
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Analysis of a Direct Time-of-Flight Sensor Architecture for LiDAR Applications

Abstract: Tel.: +41-216-954-413 † This paper is an extended version of our paper published in: Padmanabhan, P.; Zhang, C.; Charbon, E.Analysis of a modular SPAD-based direct time-of-flight depth sensor architecture for wide dynamic range scenes in a LiDAR system. Abstract:Direct time-of-flight (DTOF) is a prominent depth sensing method in light detection and ranging (LiDAR) applications. Single-photon avalanche diode (SPAD) arrays integrated in DTOF sensors have demonstrated excellent ranging and 3D imaging capabilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 27 publications
1
40
0
Order By: Relevance
“…In stationary conditions, where the probability of having a detection is constant, this equation can be rewritten as P ( DET ( k )) = P ( DET ): The equivalent rate in the continuous-time domain is P(DET)/T step for T step → 0, hence: The result converges to others reported in literature [ 18 , 19 ] and is shown also in Figure 1 , which compares this model with a Monte Carlo simulation, in case of 80 background photons within the simulation time (500 ns) and 20 signal photons within a 5 ns FWHM gaussian shape pulse, centred at a 300 ns. All simulations were performed with T step = 100 ps quantization step and 100,000 repetitions.…”
Section: Statistical Modelling Of the Spadsupporting
confidence: 76%
“…In stationary conditions, where the probability of having a detection is constant, this equation can be rewritten as P ( DET ( k )) = P ( DET ): The equivalent rate in the continuous-time domain is P(DET)/T step for T step → 0, hence: The result converges to others reported in literature [ 18 , 19 ] and is shown also in Figure 1 , which compares this model with a Monte Carlo simulation, in case of 80 background photons within the simulation time (500 ns) and 20 signal photons within a 5 ns FWHM gaussian shape pulse, centred at a 300 ns. All simulations were performed with T step = 100 ps quantization step and 100,000 repetitions.…”
Section: Statistical Modelling Of the Spadsupporting
confidence: 76%
“…It was shown that the MOF particles decorated the surface of the nanofibers and slightly decreased their diameters. The reduced sizes can be attributed to the increase in the size of the Taylor cone and decrease in the jet velocity due to a change in the viscosity of the solution 58 , 59 . Since ZIF MOFs are hydrophilic 39 , the particles tend to be pushed toward the outer layer and collected on the surface.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the entire field is illuminated at once and a detector provides both spatial resolution and timing resolution. This done in either direct time-of-flight systems (where a fast counter is used to directly measure the time-of-flight of the light 4 ) or indirect time-of-flight systems (where the outgoing light and the detector efficiency are modulated, and the phase between these modulations is measured 5 ). Flash systems offer low cost and small size.…”
Section: Methods Currently In Common Usementioning
confidence: 99%